The voice coach's toolkit - Prather, Pamela (Routledge, 2023)
"The Voice Coach's Toolkit identifies the primary professional vocal coaching opportunities and the avenues by which a student or early career coach can navigate the vocation. For purposes of this book, the Voice Coach is defined as someone who coaches the spoken voice in three precise areas: the teaching artist, the professional film/TV/theatre coach, and the professional voice-user coach. These three coaching worlds are broadly defined and each area includes in-depth interviews and practical advice from top coaches along with the author's personal expertise. This book can be read in sections or as a whole, making it as useful for early career coaches as it is for those looking to expand their vocal coaching career or vocal pedagogy students who need a broad survey of all three areas"--